Pertanggungjawaban Hukum dalam Perjanjian Kredit Perbankan terhadap Debitur Wanprestasi - Ridha, Irfan; Hanif, Iqhwatul; Vivian, Lili; Triana, Melia; Irsal, Muhammad; Ramadhan, Rafli; Marlina, Yeni; Nadila, Nadla (Jurnal Hukum dan Demokrasi (JHD), 2024)
Humans are social creatures who depend on mutual assistance to achieve their goals. Effective communication is essential to convey one's thoughts and emotions to others. Relationships can also form between individuals and financial institutions such as banks, where individuals have the opportunity to request loans and credit. However, borrowers often fail to fulfill their obligations and as a result face fines for late payments. The lack of self-confidence resulting from these lies makes it more difficult for a person to face the legal consequences of their actions. This investigation focuses on the legal consequences of bank credit agreements and the legal obligations that arise if the debtor fails to pay. This article seeks to provide a thoughtful explanation of the procedures required in recovering a failed debit transaction and the legal obligations that arise as a consequence. The research methodology used is a combination of a normative juridical approach and descriptive elements. The findings of this research are based on legal interpretations of banking laws and the legal responsibilities involved in resolving issues related to failed debit card payments. Mediation is an alternative to direct negotiations between disputing parties, which aims to facilitate resolution. If the mediation process is unsuccessful in resolving the dispute, the next action is to hand the case over to a judge to be resolved according to the agreement between the parties.